Cost-effectiveness of Evolocumab in Cardiovascular Disease: A Systematic Review - Nashmil Ghadimi; Rajabali Daroudi; Hosein Shabaninejad; Mahshad Goharimehr; Davoud Khodamorzideh; Sara Kaveh (Elsevier, 2024)
Background: With the rising burden of cardiovascular disease (CVD) and the need for cost-effective interventions, evaluating the economic implications of Evolocumab becomes crucial. Objectives: This study aimed to systematically review and evaluate the cost-effectiveness of Evolocumab in adults at risk of CVD. Methods: We performed an extensive search in Cochrane Library, EMBASE, PubMed, ProQuest, and Web of Science. The reference lists of chosen literature reviews were also examined to find suitable cost-effectiveness analyses (CEAs) of Evolocumab in patients with CVD published until March 2023. The Consolidated Health Economic Evaluation Reporting Standards statement (CHEERS) was used to assess the reporting quality. Cost-related findings were adjusted to reflect 2023 purchase power parity (PPP) values in US dollars to enable cross-study comparisons. Results: This systematic review comprised 16 studies, published between 2016 and 2023, mostly from the USA and China. Compliance with the CHEERS checklist was high in sections like abstracts, backgrounds, and objectives. However, areas like perspective (71.4%), time horizon (57.1%), and engagement with patients (14.3%) showed lower reporting rates. All studies evaluated the cost-effectiveness of Evolocumab in combination with other lipid-lowering treatments (LLTs). Notably, all studies employed model-based economic evaluations using a Markov cohort state-transition model, with a majority adopting a lifetime horizon. Most studies (10 cases) simultaneously reported both the Incremental Cost-Effectiveness Ratio (ICER) per Quality Adjusted Life Years (QALY) and the ICER per Life-Years Saved (LYS). Four studies exclusively reported ICER/QALY, and 2 studies solely focused on ICER/LYS. The ICER/ QALY exhibited a wide range (3,342.57 to 2,687,920.13 USD), with one study presenting as an outlier. Sensitivity analyses revealed factors influencing cost-effectiveness outcomes, including Low-Density Lipoprotein Cholesterol (LDL-C) levels, Evolocumab costs, and disease type, while several studies reported accepted thresholds for cost-effectiveness analysis. Conclusions: Our systematic review concludes that Evolocumab could be a cost-effective treatment, particularly for high-risk patient groups, but this varies by disease category, risk level, and evaluation methods. Future studies should investigate the economic impact's certainty and uncertainty, and consider different countries' income levels. LDL-C levels, medication costs, and CVD types are important factors affecting cost-effectiveness analysis.